Budgetary resources and local governments regarding kindergarten maintenance: Financial questions in a small-town kindergarten in the western transdanubian region (Training and Practice : Journal of Educational Sciences, 2018)
The scope of tasks and the related legislation of local governments have changed in the recent years. Financing rules related to legislative changes have been modified. The modifications of the financing rules have an impact on the maintenance and the operation of kindergartens operated by local governments. During my researches, I examined the changes in the legislation environment and state funds. I also examined how the financing of a kindergarten maintained by the local government in a small town in the Western Transdanubian region has changed, how the block grants and state funds regarding exercising functions have altered, and how supplementary subsidies of the local government – as maintainer – have contributed to the sustainable maintenance of the institutions. Research methodology: document analysis.